Assessing the impact of land use patterns on rain-flood risk in high-density urban centers: a SCS-CN model-based approach - Ma, Kun; Li, Xiaoming; Liu, Qiqi; Zhou, Wen; Li, Weiming (Frontiers in Environmental Science, 2025)
In this paper, we employ an enhanced watershed division method and the establishment of stormwater corridors, in conjunction with the SCS-CN model, to quantitatively assess flood disasters under varying rainstorm intensities in the central city of Nanjing, Jiangsu, China. The study also analyzes local adaptation practices and their effectiveness in mitigating adverse effects, taking into account the existing urban roadways and rivers. The results of our research demonstrate that this approach accurately analyzes runoff from each land unit, identifies the location, area, and propagation pattern of land units susceptible to flooding under different rainstorm intensities. Furthermore, the rain-flood corridors developed through this method effectively integrate the urban rain-flood pipeline network and provide a more precise analysis of infiltration losses during the runoff process. In conclusion, the flood safety pattern derived from this data offers valuable technical guidance for managing extreme rainstorm floods in central urban areas.